A revisit to fishmeal usage and associated consequences in Chinese aquaculture - Dong Han; Xiujuan Shan; Wenbing Zhang; Yushun Chen; Qingyin Wang; Zhongjie Li; Guofan Zhang; Pao Xu; Jiale Li; Shouqi Xie; Kangsen Mai; Qisheng Tang; et al. (Wiley Publishing Asia Pty Ltd, 2025)
China has dominated global aquaculture production for more than two decades. Aquaculture production in China increased from 24.6 million metric tons (mmt) in 2000 to 47.5 mmt in 2014, an increment of 93.1%. Along with the fast-growing aquaculture industry, aquafeed production in China increased from 5.1 mmt in 2000 to 19.0 mmt in 2014, an increment of 272.5%. However, despite the rapid increase in aquafeed production, the fishmeal usage in aquafeeds in China has remained stable over the years. Fishmeal imports into China remained relatively steady at 1.0–1.5 mmt per annum from 2000 to 2014. An often unacknowledged fact is that China contributes more than 60% to the world aquaculture production at a cost of only 25–30% of the world fishmeal output. This review attempts to explain why the fishmeal usage has not increased proportionately with the increasing aquafeed production in China from several angles: (i) the current status of fishmeal usage in Chinese aquaculture; (ii) the relationship between the decreasing dietary inclusions of fishmeal and improved feed techniques, especially the use of alternative protein sources for fishmeal; (iii) the dominance of Chinese aquaculture by low trophic level species of plants, filter feeders, herbivores and omnivores and consequent low demands for fishmeal; and (iv) the increasing price of fishmeal and the management of exploitation of wild fisheries in the main fishmeal exporting countries to China. The trends and prospects of fishmeal usage in the future in Chinese aquaculture and the associated consequences are also addressed. Like other countries, China is now actively developing both resource conservation-based capture fisheries and environment-friendly freshwater and marine aquaculture systems. Aquaculture will be the main source of aquatic food in the future and will also indirectly contribute to save the world wild fisheries, and China will be main player that will continue to contribute towards this end.